PLANNING AND DEVELOPING MULTIMEDIA WITH MACROMEDIA FLASH 8 PROFESSIONAL TO INTRODUCE INDONESIAN ART AND CULTURE - Setyaningsih, Sri; Novita, Lina; Fahmi, Nuril (UNIVERSITAS PAKUAN, 2020)
Cultural Arts Education has a role in personal formation or attitude and mentality of children in life, because arts and culture education focuses on needs child development in achieving emotional intelligence and social intelligence. Intelligent emotional is achieved by self-actualization through a sense of feeling to increase sensitivity and appreciation for the subtlety and beauty of art and culture, as well as for competence express it. Social intelligence is achieved through fostering and fostering relationships reciprocal empathic and sympathetic democracy towards Indonesian culture and uphold high human rights in order to respect diversity in society and the state as well having a national perspective with awareness of the rights and obligations of citizens.